Language policies and its impact on societal multilingualism in Sarawak - Norahim, Norazuna (Universiti Malaysia Sarawak, 2013)
The policy of having a single common language to symbolise national identity and to forge unity among various groups in multi-ethnic nations has been seen by some as marginalising the rights of minority communities to their language. It is also commonly reported in the literature as the main factor for language shift. Nonetheless, micro investigations conducted on language choice patterns of these communities concluded otherwise. This paper discusses the impact of Malaysia's language policies on societal bilingualism and language choice patterns of its community members. Using Sarawak as a case study, the paper argues that the consequences of the policy are not necessarily threatening lesser languages. In fact, it is suggested that, the policy has created greater assimilation and integration among its members. The discussion in this paper is drawn from several qualitative studies conducted on communities in the south-western part of Sarawak, namely the Bidayuh community and Iban-Malay community in Sebuyau.